POST-OPERATIVE COMPLICATIONS ENCOUNTERED BY THE STUDENTS DURING CANINE SURGERY: A RETROSPECTIVE STUDY - FAROOQ , AA; JAVID , MA; MURTAZA , S; LASHARI , MH; SHAH , MH; SALEEM , MU; BASIT , MA; ASIF , M; WAQAS , MY; AKHTAR, MS; et al. (Biological and Clinical Sciences Research Journal, 2023)
A retrospective study was conducted on analysis of procedures performed in small animal operation theatre at the Department of clinical sciences, Faculty of veterinary sciences, Bahauddin Zakariya University Multan, Pakistan, from 2009 to 2016. During this study period, 800 surgical complications were noted. The most frequent consequences seen were wound infection (21.25%), wound dehiscence (18.75%), septicemia (15.25%), and haemorrhage (15%). A slipped ligature, edema, myiasis, intestinal obstruction, and mortality were among the other problems. Laparotomy, Cystotomy, Gastrotomy, and Entrotomy had higher complication rates. Through questionnaire interviews with students, it was discovered that septic surgical procedures, inadequate use of surgical tools, and animals with low nutritional and health status were some of the factors that contributed to a high frequency of problems. The use of systemic antibiotics was necessary to treat the surgical site as an open wound to manage the post-operative problems. Recommendations are made to stop the emergence of post-operative problems when students are practicing surgery on dogs.